IMPLEMENTASI COMMUNITY BASED TOURISM DALAM MENGELOLA OBJEK WISATA GURUN TELAGA BIRU, KABUPATEN BINTAN, KEPULAUAN RIAU - Fitri, Aizah; Yulia, Nur Arini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to identify the implementation of the Community Based Tourism (CBT) approach and the obstacles encountered in managing the Gurun Telaga Biru tourist attraction. This research employs a qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of CBT involves the participation of local communities in the utilization of natural resources, community organization, and tourism management. The obstacles identified include unclear land ownership status in the tourism area, limited human resources, uneven management of tourism activities, and the influence of natural and weather conditions. Based on these findings, it is recommended to strengthen coordination with relevant institutions that have authority and understanding regarding land status, enhance community capacity through training and assistance, organize tourism activities and business locations in a more coordinated manner, and strengthen cooperation among managers, communities, and related stakeholders to support the sustainability of community based tourism management. Keywords: community based tourism, community, tourist attraction, Gurun Telaga Biru